2012
DOI: 10.1093/icesjms/fss088
|View full text |Cite
|
Sign up to set email alerts
|

Both predation and feeding opportunities may explain changes in survival of Baltic salmon post-smolts

Abstract: Mäntyniemi, S., Romakkaniemi, A., Dannewitz, J., Palm, S., Pakarinen, T., Pulkkinen, H., Gårdmark, A., and Karlsson, O. 2012. Both predation and feeding opportunities may explain changes in survival of Baltic salmon post-smolts. – ICES Journal of Marine Science, 69: 1574–1579. The survival of wild and hatchery-reared post-smolts of salmon (Salmo salar) in the Baltic Sea has declined since the 1990s. Direct observations of the processes affecting survival are, however, lacking. Here, the importance of food avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…This hypothesis is supported by negative correlations between C. harengus abundance in the Norwegian Sea and S. salar survival (Mills, 2003). Mäntyniemi et al (2012) reported a similar negative relationship between C. harengus recruitment and S. salar post-smolt survival in the Baltic Sea. After the collapse of the NSSH in 1970, post-smolt growth was particularly good in the 1970s.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This hypothesis is supported by negative correlations between C. harengus abundance in the Norwegian Sea and S. salar survival (Mills, 2003). Mäntyniemi et al (2012) reported a similar negative relationship between C. harengus recruitment and S. salar post-smolt survival in the Baltic Sea. After the collapse of the NSSH in 1970, post-smolt growth was particularly good in the 1970s.…”
Section: Discussionmentioning
confidence: 60%
“…Mäntyniemi et al . () reported a similar negative relationship between C. harengus recruitment and S. salar post‐smolt survival in the Baltic Sea. After the collapse of the NSSH in 1970, post‐smolt growth was particularly good in the 1970s.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, the abundance or energy content of key pelagic crustaceans and small pelagic fishes, on which S. salar largely prey, may have declined (Beaugrand & Reid, 2012;Friedland et al, 2013;Mills et al, 2013;Miller et al, 2014). Recent stock rebuilding in some pelagic fishes competing for similar resources to S. salar may further amplify this process (Mäntyniemi et al, 2012;Jonsson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Linking conspecific population dynamics to declining trends for focal salmonid populations has been documented in many systems (Cooney et al, 2001;Kallio-Nyberg, Jutila, Jokikokko, & Saloniemi, 2006;Kitchell et al, 2000;Mantyniemi et al, 2012;Thayer, Field, & Sydeman, 2014). Declines and fluctuations in abundance or recruitment of small pelagic fish communities have been implicated in observed decreases in survival and growth for salmonids across the Northern Atlantic and Eastern Pacific Oceans (Chaput & Benoit, 2012;Jonsson, Jonsson, & Albretsen, 2016;Thayer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%